Handling of missing data in clinical trials - Yau, Linda (Henry Stewart Talks, 2007)
The missing data problem, Missing at random (MAR), Industry experience in the handling of missing data, Last observation carried forward (LOCF), Mixed model repeated measures model (MMRM), Multiple imputation (MI), Sensitivity analysis, ICH guidelines, EMEA points to consider document, Multiple imputation inference, SAS, Solas
Archived at 2018/05/31